The Influence of Hyperglycemia at Admission on In-hospital Arrhythmia Patients with Acute Coronary Syndrome - Ahmad Fariz M.Z Zein; Sally A Nasution; Dyah Purnamasari; Arif Mansjoer (Acta Medica Indonesiana)
Aim: to determine the incidence of in-hospital arrhythmias in patients with acute coronary syndrome (ACS) andto determine the influence of hyperglycemia at admission (HA) on in-hospital arrhythmias complicating ACS. Methods: a retrospective cohort study was conducted using secondary data from medical records of patients with ACS who were admitted to ICCU RSCM, between January 1st-December 31st, 2014. Hyperglycemia at admission was defined when the blood glucose level at admission was >140 mg/dL. The in-hospital arrhythmias encompassed atrial arrhythmia, supraventricular tacchycardia (SVT), high grade AV block (HAVB), and ventricular arrhythmia, during the first seven days of hospitalization. Results: there were 232 subjects in this study. The prevalence of HA was 50.43%. The incidence of in-hospital arrhythmia was 21.55% (95% CI 16.26-26.84). In bivariate analysis, there was significant association between HA and in-hospital arrhythmia (RR 1.75; 95% CI 1.04-2.93). There were no association between type of ACS, diabetes mellitus (DM), obesity, and hypertension, with the in-hospital arrhythmias. In multivariate analysis, the adjusted OR of HA was 2.85 (95% CI 1.35-6.02), and DM was the confounding variable. Conclusion: the incidence of in-hospital arrhythmias in patients with ACS was 21.55% (95% CI 16.26-26.84). Hyperglycemia at admission may increase the risk of in-hospital arrhythmia in patients with ACS.